Dual effect of nicotine on cardiac noradrenaline release during metabolic blockade - Richardt, Gert; Brenn, T.; Seyfarth, M.; Haass, Markus; Schömig, Edgar; Schömig, Albert (Basic research in cardiology, 1994)
Nicotine-induced noradrenaline was investigated in perfused guinea pig hearts subjected to metabolic blockade that was caused either by anoxia or by cyanide intoxication. Noradrenaline, neuropeptide Y, and dihydroxyphenylethyleneglycol (DOPEG) were determined in the coronary venous overflow. Neuropeptide Y is a sympathetic cotransmitter of nordrenaline, and concomitant release of both transmitters indicates an exocytotic, calcium-dependent release mechanism, whereas neuropeptide Y overflow does not occur during nonexocytotic noradrenaline release. Nonexocytotic, calcium-independent noradrenaline release, however, is associated with an increase of DOPEG overflow, which is the main intraneuronal metabolite of noradrenaline formed by monoamine oxidase if oxygen is present.